Short Communication: Human Bone Marrow Stromal Cells Exhibit Immunosuppressive Effects on Human T Lymphotropic Virus Type 1 T Lymphocyte from Infected Individuals - Rodrigues, Evandra Strazza; De MacEdo, Mayra Dorigan; Orellana, Maristela Delgado; Takayanagui, Osvaldo Massaiti; Palma, Patrícia Vianna Bonini; Pinto, Mariana Tomazini; De Oliveira, Gislane Lelis Vilela [UNESP]; Malmegrim, Kelen Cristina Ribeiro; Slavov, Svetoslav Nanev; Covas, Dimas Tadeu; Kashima, Simone (SAGE Publications, 2019)
Human multipotent mesenchymal stromal cells (MSCs) display immunoregulatory functions that can modulate innate and adaptive cellular immune responses. The suppressive and immunomodulatory activities of MSCs occur through the action of soluble factors that are constitutively produced and released by these cells or, alternatively, after MSC induction by stimuli of inflammatory microenvironments. However, to date the contribution of MSCs in the inflammatory microenvironment resulting from viral infection is unknown. In our study, we evaluated the MSC immunosuppressive effect on human T lymphotropic virus type 1 (HTLV-1) infected T lymphocytes. To evaluate if MSC immunoregulation can influence the proliferation of HTLV-1 infected T lymphocytes, we compared the proliferation of lymphocytes obtained from HTLV-1 infected and healthy individuals cocultured in the presence of MSCs. It was observed that the lymphoproliferative inhibition by MSCs on infected lymphocytes was similar compared to the cells obtained from healthy individuals. In addition, this suppressive effect was related to a significant increase of indoleamine-2,3-dioxygenase and prostaglandin E2 gene expression (p ≤.05). Furthermore, the HTLV-1 pol gene was less expressed after coculturing with MSCs, suggesting that the MSC immunoregulation can have effective suppression on HTLV-1 infected T cells. In conclusion, this study suggests that MSCs could be involved in the immunomodulation of the HTLV-1 infected T lymphocytes.
Keywords: gene expression; HTLV-1; immunoregulation; MSC